Electron-induced chemistry of surface-grown coordination polymers with different linker anions. Issue 5 (18th January 2019) - Ahlenhoff, Kai; Koch, Sascha; Emmrich, Daniel; Dalpke, Raphael; Gölzhäuser, Armin; Swiderek, Petra
Abstract : The structure of the linker anions is decisive for the efficiency and outcome of electron-induced chemistry in surface-grown layers of copper(ii ) containing materials. Abstract : Electron beam processing of surface-grown coordination polymers is a versatile approach to the fabrication of nanoscale surface structures. Depending on their molecular components, these materials can be converted into pure metallic particles or they can be activated to become a template for the spatially selective decomposition of suitable gaseous precursor molecules and subsequent autocatalytic growth of deposits. However, insight into the fundamental electron-induced chemistry for such processes has been scarce so far. Therefore, we investigated the electron-induced reactions of three self-assembled copper-containing materials, namely, copper(ii ) oxalate, copper(ii ) squarate, and copper(ii ) 1, 3, 5-benzenetricarboxylate (HKUST-1) which were grown on the surface of self-assembled monolayers of mercaptoundecanoic acid in a layer-by-layer approach from copper(ii ) acetate and various linker molecules. Changes incurred to these materials during electron irradiation were monitored by four complementary techniques. Reflection absorption infrared spectroscopy (RAIRS) and X-ray photoelectron spectroscopy (XPS) were used to identify the chemical species that are formed upon electron exposure. The temporal evolution of electron-stimulated desorption (ESD) of neutral volatile fragments was monitored to reveal the kinetics governing the decomposition of the different materials. Furthermore, the morphology was investigated by helium ion microscopy (HIM). A detailed analysis of the results for the different linker molecules provides new insights into the electron-induced chemistry of such surface-grown layers.